Enhancing physical education through blended learning: Impact on student self-efficacy and performance - Yan, Ge; Abdullah, Borhannudin; Abu Saad, Hazizi (Prof.Dr. İskender AKKURT, 2025)
This study evaluates how blended learning influences student outcomes in physical education through self-efficacy and performance assessments. A mixed-methods approach was used for data collection, combining quantitative pre-and post-intervention assessments of student performance (measuring changes in fitness, skills, and academic outcomes) with qualitative interviews to gather insights on student perceptions of self-efficacy and blended learning experiences. A control group was established to compare the effects of traditional physical education methods with blended learning. Ten students were randomly selected from the student population to participate in this study. Statistical techniques were employed to compare and correlate pre-and post-intervention results with qualitative data to gain a comprehensive understanding of how outcomes are influenced by blended learning. This study aims to add empirical knowledge on incorporating blended learning into physical education and its practical applications. It offers recommendations for educators and policymakers on effectively using blended learning strategies to optimize student self-efficacy in physical education settings.